2021
DOI: 10.1590/0366-69132021673843072
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb2+ and Zn2+ using modified Chocolate B clay: a study using statistical analysis, equilibrium isotherms, and adsorption kinetics

Abstract: In this work, natural and thermally modified Chocolate B clays were used for batch adsorption of Pb 2+ and Zn 2+ from an aqueous solution. The materials were characterized by X-ray diffraction, X-ray fluorescence spectroscopy, nitrogen adsorption, and cation exchange capacity. The tests were performed in a finite bath following a 2 2 factorial design, with the variables: pH and initial concentrations of metal. Results revealed that the thermal treatment caused alterations on the Chocolate B clay structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The 20.6% fire loss for Bent-R is probably related to moisture, coordinated and adsorbed water losses, organic matter burning, carbonate decomposition, and structural destruction of clay minerals. In general, it was observed that Bent-R has a typical chemical composition of bentonite clays [23,24]. Bent-Na presented all constituents detected in natural clay; the sodium present resulted from sodium functionalization.…”
Section: Characterization Of Claysmentioning
confidence: 96%
“…The 20.6% fire loss for Bent-R is probably related to moisture, coordinated and adsorbed water losses, organic matter burning, carbonate decomposition, and structural destruction of clay minerals. In general, it was observed that Bent-R has a typical chemical composition of bentonite clays [23,24]. Bent-Na presented all constituents detected in natural clay; the sodium present resulted from sodium functionalization.…”
Section: Characterization Of Claysmentioning
confidence: 96%